2009
DOI: 10.1108/10650740910984637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating technology resistance and technology satisfaction on students' performance

Abstract: PurposeUsing the extended task‐technology fit (TTF) model, this paper aims to examine technology resistance, technology satisfaction and internet usage on students' performance.Design/methodology/approachThe study was conducted at Universiti Teknologi MARA, Johor, Malaysia and questionnaires were distributed to 354 undergraduate students.FindingsThe structural equation modelling (SEM) results indicate that technology satisfaction and the internet usage significantly explains the variance on students' performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
9
22
0
Order By: Relevance
“…It is the degree to which user believes that it would be free of efforts by using a particular system [13]. There is lots of research which provides evidence of the significant effect of ease of use on intention to use [13,21,23,26,34]. Among the potential adopters of software, PEU has a positive effect on intention to adopt [21].…”
Section: Perceived Ease Of Use (Peu)mentioning
confidence: 99%
“…It is the degree to which user believes that it would be free of efforts by using a particular system [13]. There is lots of research which provides evidence of the significant effect of ease of use on intention to use [13,21,23,26,34]. Among the potential adopters of software, PEU has a positive effect on intention to adopt [21].…”
Section: Perceived Ease Of Use (Peu)mentioning
confidence: 99%
“…Goodhue and Thompson (1995) posit that full picture of task characteristics in the use of any technology within organizations requires considering if the technology involved fits the task or not. TTF views task-context by its complexity and interdependences (Goodhue & Thompson, 1995) and explains that fitting task demands that technology's fit capabilities make for faster adoption and superior services (Norzaidi and Salwani, 2009;Alatawi et al, 2012;D'Ambra et al, 2013). For task complexity, scholars (Lin & Huang, 2008;Zhou et al, 2012) posit that technology is adopted to the extent that it streamlines the structure of complex tasks and their interrelationships in meeting the task demands.…”
Section: Task Technology Fit (Ttf)mentioning
confidence: 99%
“…Task interdependence explains the degree of interconnectivity amongst tasks and organizational units (Goodhue & Thompson, 1995), given that interconnectedness between jobs/activities explains that task's successes depend largely on the performance of intra and inter units/divisions supportive tasks (Norzaidi & Salwani, 2009;D'Ambra et al, 2013). When people and tasks are interdependent, people seek real-time exchange of information (Alatawi et al, 2012) and show likelihood to adopt technologies with the capabilities to coordinate, develop effective task performance strategies, clarify task assignments, obtain performance feedback and make informed decisions (Goodhue & Thompson, 1995;Andres & Zmud, 2002).…”
Section: Task Technology Fit (Ttf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The link between the development of information technology and job satisfaction is shown by the research results of [20] which stated that the frequency and time of technology use have an impact on user satisfaction in the context of Internet technology in Malaysia. Meanwhile, other studies have found that the frequency and time of technology use can predict user satisfaction [21,22,23].…”
Section: Organizational Culturementioning
confidence: 99%